DINAMIKA KETENAGAKERJAAN DALAM PERSPEKTIF DEMOGRAFI DAN SOSIAL EKONOMI DIKABUPATENLOMrnOKBARAT - YB. Widodo (Jurnal Kependudukan Indonesia, 2009)
The study on "The Labour Force Dynamic in the Perspective of Demographic and Social Economic Structural Change in West Lombok" is the early phase of the four years (2006-2009) study. The aim of this study is to analyze the employment growth and changes in demographic and social economic structure in West Lombok, using qualitative approach. The study uses the data gathered from samples of population villages on Sekotong District - West Lombok. This study shows, that to meet the pressing competition for capable manpower in the global economy, agroindustry must be developed in accordance with local potentials. This policy should create more jobs and increase the income and welfare of the local population. This problem needs to be addressed by adopting entirely new approaches to meet basic employment and income requirements for the larger segment of the disirict population. On the other hand, new methods can be devised to make market and institutional services more accessible to farmers welfare and labour market.Keywords: Demography; employment, rural areas: West Lombok.